UPAYA PEMERINTAH MILITER JEPANG MEMBENTUK KARAKTER MILITANSI PEJUANG BANGSA - Laxsmi Desiyana; Iskandar Syah; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2013)
Japanese military government effort form Indonesian warrior militancy character year 1942-1945. During the reign of Japanese in Indonesia, there are three military governments that is, 25th army military for Sumatra, 16th army military for Java and Madura, 2nd south armada navy military for Sulawesi, Kalimantan, and Maluku. The purposes of this research to find out the kinds of efforts of Japanese military government in forming the warrior nation militancy in Indonesia in 1942-1945 through the groups of semi-military and through the groups of military. The methods of this research were historical and descriptive. Data analysis technique used is qualitative data. This study results indicate that the early establishment of military agency (Seinenden, Keibodan) and Japanese semi-military (Heiho, PETA, Barisan Pelopor, Hisbullah) is to help Japanese face the allies. It can be concluded that the military training given by Japanese have formed the Indonesian warrior militancy character.Keywords : Japanese military, Japanese semi-military, Indonesian warrior militancy